Designing human-centered 3D GIS interface and interaction model to support agriculture commodity selection - Maulana, Hanhan; Kanai, Hideaki (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this study is to design an interface and an interaction model using user-centered Design approach. The model-built first aim is to assist the development process of a 3-dimensional geographic information system (3D GIS). The second aim is to ensure that the system that is built meets the needs of the user. GIS has been applied in various fields. In the agriculture field, GIS is often used to assist land evaluation and commodity selection. 3D GIS can provide map visualizations that are similar to actual earth topography. This advantage can minimize the user's cognitive load when using the map. Developing 3D GIS requires more complex components than 2D GIS. This study proposes an interface and interaction model for 3D GIS in scope of agricultural commodities selections. This study has five main stages. The first stage is software requirements Analisys. The second stage is data and content analysis. At this stage, data analysis is carried out to then build a data model to manage geocontent. The third stage is User Interface design. At this stage, an interface model is created as guidelines to arrange the 3D map layout. The fourth stage is the development of the interaction model to analysis of potential user actions and feedback of the system. The last stage is prototype development and evaluation. The prototype is evaluated by involving farmers to measure the adequacy of the data. A heuristic evaluation focused on eight statements was carried out. Based on the evaluation process, in general, most users agree with the statements made. It means that the model built meets the needs of the user. This model is expected to make it easier for software developers to build 3D GIS and ensure the farmer’s need in the sistems are meets. It’s hoped that combining visual elements and interaction can increase the usability level of 3D GIS.